Handgrip Strength of Public Works Personnel in West Jakarta - Alvina Alvina; Pusparini Pusparini; Mario Mario; Yasmine Mashabi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Public Works Personnel (PWP) in Jakarta perform their routine duties manually instead of using equipment. Handgrip strength (HGS) measures maximum hand strength as a quality indicator for muscle strength and mass. Factors affecting muscle strength are age, sex, body mass index (BMI), waist circumference (WC), and hip circumference (HC). Increased fasting blood glucose (FBG) is also associated with muscle quality, muscle strength, and physical performance. This study aimed to determine the factors associated with handgrip strength in PWP. A total of 192 male PWP from the Cengkareng district were recruited by simple random sampling. The collected data were demographics, BMI, FBG, WC, HC, and HGS. Statistical analysis was done using Pearson’s correlation test and multiple regression analysis. There was a significant positive correlation of BMI, WC, and HC with HGS (p=0.006; r=0.20, p=0.009; r=0.19, and p=0.005; r=0.20) and a significant negative correlation between age and HGS (p=0.008; r=-0.19) but not between FBG and HGS (p=0.847). Multiple regression analysis showed height, BMI, and HC positively predicting HGS (R2=0.19). Handgrip strength of public works personnel is associated with BMI, age, waist circumference, and hip circumference, but not with fasting blood glucose. Height, BMI, and hip circumference predict handgrip strength.